2021
DOI: 10.3390/genes12122021
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis by Array Comparative Genomic Hybridization in Fetuses with Cardiac Abnormalities

Abstract: Congenital heart defects (CHDs) appear in 8–10 out of 1000 live born newborns and are one of the most common causes of deaths. In fetuses, the congenital heart defects are found even 3–5 times more often. Currently, microarray comparative genomic hybridization (array CGH) is recommended by worldwide scientific organizations as a first-line test in the prenatal diagnosis of fetuses with sonographic abnormalities, especially cardiac defects. We present the results of the application of array CGH in 484 cases wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…22q11.2DS has a reported contemporary live birth incidence of 1:2148 [2] and even higher prenatal prevalence estimates of 1:992 unselected pregnancies (those without identified cardiac anomalies) and 1:1497 miscarriages [3,4], regardless of maternal age. In recent studies, a 22q11.2 deletion was found in 1:19 pregnancies undergoing diagnostic testing for cardiac anomalies and 1:93 for all indications [5]. However, many children and adults with 22q11.2DS do not have congenital heart disease (CHD) or other anomalies that would be readily detectable on routine fetal ultrasonography [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…22q11.2DS has a reported contemporary live birth incidence of 1:2148 [2] and even higher prenatal prevalence estimates of 1:992 unselected pregnancies (those without identified cardiac anomalies) and 1:1497 miscarriages [3,4], regardless of maternal age. In recent studies, a 22q11.2 deletion was found in 1:19 pregnancies undergoing diagnostic testing for cardiac anomalies and 1:93 for all indications [5]. However, many children and adults with 22q11.2DS do not have congenital heart disease (CHD) or other anomalies that would be readily detectable on routine fetal ultrasonography [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A further 74 articles were secondarily excluded from the quantitative analysis. Of these, 38 did not provide quantitative data [ 6 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ], in 22 articles it was not possible to infer a quantitative analysis of incremental yield of CMA over standard karyotyping [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 …”
Section: Resultsmentioning
confidence: 99%
“…In general, unbalanced chromosomal aberrations accompanied CVAs in 47.5% of cases, which is more than previously reported. In the study by Kowalczyk et al [ 37 ], the aCGH technique revealed aneuploidies and structural aberrations in 37% of fetuses with heart anomalies. In our study, the most common chromosomal aberrations associated with CVAs were trisomies 21, 18, and 13, and triploidy, while the Pediatric Cardiac Genomics Consortium did not report trisomies 18 and 13 and triploidy as common findings [ 7 ].…”
Section: Discussionmentioning
confidence: 99%